ART AS A LANGUAGE OF CHILDHOOD: EDUCATIONAL PRACTICES IN PRIMARY SCHOOLS IN INDIA - Prashant S. Mothe (SMART: Journal of Multidisciplinary Educational, 2024)
This study investigates the role of art as a “language of childhood” in Indian primary schools, aiming to understand how children use art to express emotions, cultural identity, and abstract ideas while supporting cross-disciplinary learning. Employing a literature-based research method, the study synthesizes recent peer-reviewed journal articles, policy documents, and empirical studies from 2019–2025 to examine art integration practices, teacher preparedness, and resource disparities across urban, rural, and semi-urban schools. The findings reveal that urban private schools exhibit higher student engagement and creativity due to better access to trained teachers and materials, while rural government schools face significant challenges related to infrastructure, limited teacher training, and curriculum constraints. The study also identifies culturally responsive approaches and the innovative use of local art materials as key strategies for promoting equitable access and enhancing expressive learning across diverse contexts. The novelty of the research lies in framing art not merely as a curricular subject but as a systemic medium for cognitive, emotional, and socio-cultural development, emphasizing its potential as a cross-disciplinary pedagogical tool. Additionally, the study highlights the importance of teacher professional development, resource allocation, and contextual adaptation to maximize the impact of art in primary education. In conclusion, this research contributes both conceptual and practical insights, demonstrating that art serves as an essential language through which children learn, communicate, and construct meaning, offering valuable implications for educators, policymakers, and curriculum designers seeking to enhance creativity and holistic development in primary education worldwide.